Relationship Between Anabolic–Androgenic Steroid Use, Aggression, and Narcissism in Male Bodybuilders - Eren Ceto; Pembe Hare Yigitoglu; Hasan Ulas Yavuz (Medicina)
Background and Objectives: The use of anabolic–androgenic steroids (AASs) by competitive and recreational athletes has been studied and well documented. There are numerous studies showing its effects on personality traits and risky behaviors like aggression. The relationship between AAS use, aggression, and narcissism is complex and intricate. We examined this relationship in male bodybuilders who use AASs. Materials and Methods: A total of 319 healthy subjects aged 18–44 years (33.4 ± 9.4) who have been regularly training at bodybuilding for at least 3 years participated voluntarily in the study and completed a demographic data inventory, the Five-Factor Narcissism Inventory Short Form (FFNI-SF), and the Buss–Perry Aggression Scale anonymously. Demographic data were given as percentages, comparisons of aggression and narcissism scores according to AAS use were performed by using an independent sample t test, and effects of narcissism and aggression levels on AAS use was assessed by using logistic regression analysis. All analyses were performed by using SPSS Statistics 22.0. Results: Results showed that AAS users had significantly higher scores on the overall FFNI-SF Scale (p < 0.001) and all sub-dimensions of narcissism (p < 0.001) and on the overall Buss–Perry Aggression Scale (p < 0.001) and all sub-dimensions of aggression (p < 0.001). It was also shown that there were significant and positive correlations between the FFNI-SF overall score (p < 0.001) and both the vulnerable narcissism and grandiose narcissism sub-dimensions (p < 0.001) and the scores of the Buss–Perry Aggression Scale (p < 0.001), physical aggression (p < 0.001), anger (p < 0.001), hostility (p < 0.001), and verbal aggression (p < 0.001) sub-dimensions. Conclusions: These results show a strong relation between AAS use, narcissism, and aggression in bodybuilders. However, it is not clear whether AAS use leads to aggression and narcissism or whether narcissistic and/or aggressive people tend to use AASs. Furthermore, including a lot of potential third variables shows that it does not have to be either one or the other way around. There is a need to conduct future studies to determine this causality.